2016
DOI: 10.1027/0227-5910/a000369
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Adolescents Self-Harm?

Abstract: Background. Given the high rates of self-harm among adolescents, recent research has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 45 publications
4
21
0
9
Order By: Relevance
“…Low self-esteem is associated with suicidal ideation and behaviour in LGB individuals (Hegna & Wichstrøm, 2007;Ybarra et al, 2015). Self-harm may occur as a means of coping with, avoiding or escaping from highly aversive internal states, including chronically low self-esteem (Rasmussen, Hawton, Philpott-Morgan, & O'Connor, 2016;Taylor et al, 2018). For NSSI, more specifically, motives of selfpunishment are highly endorsed (41-62% of people who engage in NSSI; Taylor et al, 2018).…”
Section: Psychological Correlates Of Self-harm Within Gay Lesbian Anmentioning
confidence: 99%
“…Low self-esteem is associated with suicidal ideation and behaviour in LGB individuals (Hegna & Wichstrøm, 2007;Ybarra et al, 2015). Self-harm may occur as a means of coping with, avoiding or escaping from highly aversive internal states, including chronically low self-esteem (Rasmussen, Hawton, Philpott-Morgan, & O'Connor, 2016;Taylor et al, 2018). For NSSI, more specifically, motives of selfpunishment are highly endorsed (41-62% of people who engage in NSSI; Taylor et al, 2018).…”
Section: Psychological Correlates Of Self-harm Within Gay Lesbian Anmentioning
confidence: 99%
“…Self-harm (SH) is characterized by a wide range of behaviours and intentions, including attempted hanging, impulsive self-poisoning, and superficial cutting [ 1 ], which aim to relieve a terrible state of mind [ 2 ] or communicate stress [ 3 ]. SH behaviour is a significant public health issue worldwide with a high prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Yet motivations for STB have received less attention. Studies designed specifically to identify why youth engaged in STB reported reasons such as conflict with a family member, self-punishment, and escape from pain (Arkins et al, 2013;Kene & Hovey, 2014;Rasmussen, Hawton, Philpott-Morgan, & O'Connor, 2016). However, these studies were either based in European countries or included U.S. adults in psychiatric hospitals.…”
mentioning
confidence: 99%